2019
DOI: 10.3389/fneur.2019.00290
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Aldehyde dehydrogenase-2 Polymorphisms and Risk of Alzheimer's Disease and Parkinson's Disease: A Meta-Analysis Based on 5,315 Individuals

Abstract: Objective: A number of studies have reported that aldehyde dehydrogenase-2 ( ALDH2 ) polymorphisms maybe associated with the risk of Alzheimer's disease (AD) and Parkinson's disease (PD). However, the results of such studies are inconsistent. We therefore conducted a meta-analysis to clarify the association between ALDH2 polymorphisms and the risk of AD and PD. Methods: Five online databases were searched and the relevant studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 43 publications
2
24
0
3
Order By: Relevance
“…AD and PD (Chen et al, 2019;Joshi et al, 2019). Even though the growing body of literature suggests the potential neuroprotective effects of low to moderate dose of ethanol, factors such as genetic variation in metabolism of ethanol should be further explored in its role of neuroinflammation and neurodegeneration.…”
Section: Alcohol: Could It Be Neuroprotective?mentioning
confidence: 99%
See 1 more Smart Citation
“…AD and PD (Chen et al, 2019;Joshi et al, 2019). Even though the growing body of literature suggests the potential neuroprotective effects of low to moderate dose of ethanol, factors such as genetic variation in metabolism of ethanol should be further explored in its role of neuroinflammation and neurodegeneration.…”
Section: Alcohol: Could It Be Neuroprotective?mentioning
confidence: 99%
“…In reality, most of the alcohol dependent patients practice episodic drinking pattern with more than one type of alcoholic drinks, therefore assessment of the effects of any specific types of alcohol containing drinks on their cognitive performance or neurological features is nearly impossible. In addition, rate of alcohol metabolism also varies among the individuals and impairment in metabolism of aldehydes (one of the by-products of ethanol metabolism) due to mutation in aldehyde dehydrogenase 2 (ALDH2) was identified as a risk factor for AD and PD ( Chen et al, 2019 ; Joshi et al, 2019 ). Even though the growing body of literature suggests the potential neuroprotective effects of low to moderate dose of ethanol, factors such as genetic variation in metabolism of ethanol should be further explored in its role of neuroinflammation and neurodegeneration.…”
Section: Aud-induced Neurodegenerative Diseasementioning
confidence: 99%
“…Despite the unpleasant reaction to acetaldehyde accumulation, 17–27% of individuals with this ALDH2 mutation consume alcoholic beverages excessively; up to 3 drinks per day or 7 drinks per week for women and up to 4 drinks per day or no more than 14 drinks per week for men [3]. Additionally, a recent meta-analysis correlated ALDH2*2 genotype and AD development; six case-control studies involving 2840 subjects indicated an increased risk of the ALDH2*2 genotype for AD [10].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier findings from our group and others indicated a beneficial role for ALDH2 in cardiovascular diseases, including diabetes mellitus, ischemia reperfusion injury, atherosclerosis, stroke, sepsis, and obesity, through regulation of autophagy. 21 , 30 – 32 , 59 , 60 In the context of neurodegenerative diseases, ALDH2 deficiency was reported to be correlated with AD incidence, 23 , 25 although contradictory findings were noted, disproving the correlation between ALDH2 and AD risk in humans. 28 , 34 , 61 The possible role for ALDH2 in AD pathology is consistent with low ALDH2 activities in AD patients and APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%